Hubungan Dukungan Sosial, Status Sosial Ekonomi dan Usia dengan Kesejahteraan Psikologis Pasien Pasca Covid-19 - Arief Budiman; Jidan Ramadhan; Nanda Nur Hidayah; Putri Dwi Hasmi; Rafika Sandra (Fakultas Ilmu Kesehatan, 2023)
Introduction: : Coronavirus Disease 2019 is an infectious disease that causes severe acute respiratory syndrome. During this COVID-19 pandemic, it has a negative impact on physical and psychological health. In Indonesia, there is a negative public stigma regarding post-COVID-19 patients. People tend to isolate someone who has been declared cured, ostracize groups that are considered easy to spread the COVID-19 virus. The existence of negative stigma from society and the environment can be burdensome for patients who have recovered to be able to return to normal activities, this will generally affect their psychological well-being. Purpose: to determine what factors were associated with the psychological well-being of post-Covid-19 patients. Method: This research method uses a correlation descriptive research design with a cross sectional approach. The population in this study were 328 post-COVID-19 patients and a sample size of 255 respondents using the incidental sampling technique. Data collection was carried out from May to October 2021 in the Sambutan Samarinda health center work area by using questionnaires. Statistical analysis test using frequency distribution and central tendency, while for bivariate test using Spearman Rank. Result: The results of the study based on the Spearman Rank test there was a significant relationship between sosial support, socioeconomic status, age factor and psychological well-being of post-covid-19 patients with a p value of 0.00. Conclusion: the factors of sosial support, socioeconomic status and age have a significant relationship to the psychological well-being of post-covid-19 patients with a very strong relationship and a positive direction, meaning that the higher the sosial support, socioeconomic status and age of a person, the the better the psychological well-being.